Global Policy Studies - Nagel, Stuart S. author. aut Link
XIX, 274 p.
Keywords: An analysis of international interactions which have been designed to deal with shared policy problems. Such problems include pollution, trade, common property problems, health and education. This subject crosses the fields of international relations and comparative public policy studies.